Application of a 3D hydrogel-based model to replace use of animals for passaging patient-derived xenografts - Jones, Sal (2021)
Currently, in vivo mouse models are the gold standard for testing cancer treatments before progression to human trials, often using tissue derived directly from patient tumours (patient-derived xenografts, PDXs) propagated in mice to generate sufficient cells for an experiment. A 3D in vitro system for tumour passage would reduce animal use and provide an alternative means of expansion, with the additional benefit of being capable of maintaining a human signalling environment throughout.